Caminhos da docência no Instituto Federal Farroupilha: da formação aos primeiros anos da carreira na educação profissional e tecnológica - Avinio, Carina de Souza (2014)
This study has as its theme the ways of teaching in Basic Education, Technical and Technological (EBTT), finding themselves tied to the line of research: training, knowledge and Professional Development of the program of postgraduate education (PPGE) at the Federal University of Santa Maria (UFSM). The research aims to understand the General configuration of the ways of teaching, pedagogical training to the first years of operation, in the scenarios of Basic Education, Technical and Technological (EBTT), with emphasis on operations in the upper Courses of Technology (CST). The qualitative approach and has developed research as a tool were conducted interviews with narratives teachers alumni active in early period of teaching at ETH Ragamuffin and attended the Graduate Special Program PEG, teacher training for vocational education, offered by UFSM. The data were analyzed and interpreted through Discursive Textual Analysis (MORAES; GALIAZZI, 2007). On construction of conceptual reflective array include authors such as: Cunha (2010); M (2009); Isaia (2006); Isaia; Bolzan (2010) who conceptualize about the early years of teaching and its complexity. Thus, we consider that this research has contributed towards meeting the dilemmas faced by the teachers to EBTT join in and take classes CST; describe the training needs that have arisen in the teaching career and in confronting the specificities of the CST; analyze the contributions of training of graduates from the PEG at the beginning of the professional experience teaching in Higher Education (CST). The search results served as reflective analysis for issues related to this area of training as well as highlight significant information regarding the training and reflective suggestions to contribute to the formation of professional technological education.